2020
DOI: 10.18433/jpps30967
|View full text |Cite
|
Sign up to set email alerts
|

Medical Marijuana Effects in Movement Disorders, Focus on Huntington Disease; A Literature Review

Abstract: Purpose: We aimed to comprehensively evaluate the effects of medical marijuana on symptoms that are relevant to movement disorders with a focus on Huntington disease (HD). Methods: A systematic review by literature search through PubMed and EBSCO electronic databases was conducted for relevant studies reported after 2002 on the effects of medical marijuana or cannabis use on tremor, spasm, spasticity, chorea, sleep quality and HD-specific rating scales. Study selection, quality assessment and data extraction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Chronic EAE is actively induced by immunization of C57BL/6 mice with myelin oligoden-drocyte peptide (MOG ) [58], with options for utilizing transgenic mice that provide specific immunogenetic backgrounds [55,59]. A remitting-relapsing form of EAE is actively induced by immunization of SJL/J mice with intact protein or peptides from either myelin basic protein (MBP) [60][61][62][63] or proteolipid protein (PLP [139][140][141][142][143][144][145][146][147][148][149][150][151] ) [64]. Monophasic EAE can be induced by immunization of Lewis rats with MBP 68-86 , and chronic disease can be induced in common marmoset and rhesus macaque non-human primates with MOG 34-56 [55,65,66].…”
Section: Experimental Animal Models Of Msmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic EAE is actively induced by immunization of C57BL/6 mice with myelin oligoden-drocyte peptide (MOG ) [58], with options for utilizing transgenic mice that provide specific immunogenetic backgrounds [55,59]. A remitting-relapsing form of EAE is actively induced by immunization of SJL/J mice with intact protein or peptides from either myelin basic protein (MBP) [60][61][62][63] or proteolipid protein (PLP [139][140][141][142][143][144][145][146][147][148][149][150][151] ) [64]. Monophasic EAE can be induced by immunization of Lewis rats with MBP 68-86 , and chronic disease can be induced in common marmoset and rhesus macaque non-human primates with MOG 34-56 [55,65,66].…”
Section: Experimental Animal Models Of Msmentioning
confidence: 99%
“…Cannabis-based medicine has long been known to be useful in pain management including central pain in multiple sclerosis and post-operative pain [143,144]. Promising benefits of cannabis use and medical marijuana have also been observed for relief of neurologic symptoms in patients with movement disorders, including Parkinson disease and Huntington disease [145]. Furthermore, oral CBD has been used for the treatment of drug-resistant seizures in children with tuberous sclerosis (TSC) [146], and Epidiolex ® (pure CBD) has been approved for the treatment of intractable epilepsy in patients with developmental epileptic encephalopathies [147] including Dravet syndrome and Lennox-Gastaut syndrome (LGS).…”
Section: ⊕⊕⊕mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the participant feedback, it was suggested that improved physical mobility may be an additional benefit experienced attributed to the reduction in pain symptoms with medical cannabis usage. Although there is limited literature on medical cannabis and its effects on mobility, a review assessing medical cannabis in patients with Huntington's Disease found significant improvement in motor symptoms including tremors and rigidity after medical cannabis treatment (Akinyemi et al, 2020). Further research would be beneficial to determine the physical benefits and potential changes in motor functioning with medical cannabis.…”
Section: Discussionmentioning
confidence: 99%
“…Positive effects have also been shown for symptoms such as spasticity and tremor, although patients that presented these symptoms had other neurodegenerative diseases and not HD (e.g., spasticity improvement was demonstrated in patients with autoimmune demyelinative disease and MS, while tremor was improved in patients with PD following administration of medical marijuana). The positive effects shown in patients with HD were improvements in chorea; improvements in the neuropsychiatric index; and trend for improvements in the Unified Huntington's Disease Rating Scale motor score, the dystonia subscore and behavior score [151].…”
Section: Cannabinoids and Huntington's Diseasementioning
confidence: 99%